Determination of Total Protein and Calcium in Gingival Mesenchymal Stem Cell-Conditioned Medium - Banun Kusumawardani; Intan Julita Purnamasari; Dea Ajeng Pravita Suendi (Universitas Muhammadiyah Yogyakarta, 2021)
Gingival mesenchymal stem cell-conditioned medium (GMSC-CM) is a conditioned medium obtained from cultured gingival mesenchymal stem cells. GMSCs are easily isolated from gingival tissue, whereas gingival tissue is easily obtained by minimally invasive techniques. On the other hand, CM contains proteins, cytokines, chemokines and growth factors that play an important role in osteogenic differentiation.This study aims to determine the total protein and calcium levels in GMSC-CM.GMSCs were grown in culture media with 10% of FBS. CM of GMSC was obtained from the media collection process with a 0.22 µm filter and concentrated with a centrifugal filter to obtain a concentrated GMSC-CM. The concentration of total protein was performed by bicinchoninic acid protein assay on GMSC-CM and concentrated GMSC-CM. Calcium level was performed by atomic absorption spectroscopy method. The results arethat GMSC-CM had a total protein concentration of 2502±0.06 µg/ml, and the concentratedGMSC-CM was 1.912±0.08 μg/ml.The calcium level of GMSC-CM was 0.009% and concentratedGMSC-CM was 0.009%. It can be concluded thatGMSC-CM had a high concentration of total protein and calcium. These parameters were used to develop bioprocesses to enhance the production of GMSC-CM, which will support the implementation of cell-free therapy for tissue regeneration.